A view from a different angle: investigating the significance of tattan spines from a small mammals’ visual point of view using imageJ - Nik Fadzly,; Asyraf Mansor,; Rahmad Zakaria,; Syed Ahmad Edzham, (Universiti Kebangsaan Malaysia, 2014)
Rattans are one of the most unique and economically important plants for most tropical countries. There is however, a lack of interest in the specific study of the rattan spines. In this paper, we tested a new hypothesis concerning the functional role of rattan spines. We proposed that rattan spines also serve as a visual deterrent against herbivores or seed predators. In our proposed method we used an Imaging software, ImageJ, to measure the spine area of four species of rattan (Calamus insignis, Myrialepis schortechinii, Plectocomiopsis geminiflorus and Calamus caesius) from two different orientations (root to shoot and vice versa). Our results showed that rattan spines were very heterogeneous and highly variable between different species. One common trait that the rattan spines share is that spine area measurements of shoot to root (ShR) are larger than root to shoot (RH) orientation. We propose that the downwards spine angle might be specifically designed to discourage climbing leaf and seed predators.